2022
DOI: 10.1101/2022.10.27.22281470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rare coding variants inCHRNB2reduce the likelihood of smoking

Abstract: Human genetic studies of smoking behavior have been so far largely limited to common variations. Studying rare coding variants has potential to identify new drug targets and refine our understanding of the mechanisms of known targets. We performed an exome-wide association study (ExWAS) of smoking phenotypes in up to 749,459 individuals across multiple ancestries and discovered a protective association signal in CHRNB2 that encodes the β2 subunit of α4β2 nicotine acetylcholine receptor (nAChR). Rare predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Notably, effect sizes for identified genes from collapsing analysis are lower than expected from previous studies. Considering that HR estimates from subsequent survival analysis were larger and more consistent with previous reports, we hypothesize that the comparatively smaller effect sizes observed during the initial gene discovery phase were primarily due to the usage of saddle point-approximationcorrected logistic mixed-model approach implemented in the SAIGE-GENE+ software, which might yield slightly conservative effect estimates, particularly when assessing significance for binary traits with imbalanced case-control ratios 39 .…”
Section: Discussionsupporting
confidence: 78%
“…Notably, effect sizes for identified genes from collapsing analysis are lower than expected from previous studies. Considering that HR estimates from subsequent survival analysis were larger and more consistent with previous reports, we hypothesize that the comparatively smaller effect sizes observed during the initial gene discovery phase were primarily due to the usage of saddle point-approximationcorrected logistic mixed-model approach implemented in the SAIGE-GENE+ software, which might yield slightly conservative effect estimates, particularly when assessing significance for binary traits with imbalanced case-control ratios 39 .…”
Section: Discussionsupporting
confidence: 78%
“…Most recently, in a large sample of both current and former smokers (~ 110K) and never smokers (~ 375K), an exome-wide association study (ExWAS) showed that rare predicted loss-of-function and likely deleterious missense variants in CHRNB2 in aggregate were associated with a 35% decreased odds (protective) for smoking more than 10 cigarettes per day. An independent common variant of CHRNB2 , rs2072659, also showed a protective effect for heavy smoking 33 .…”
Section: Introductionmentioning
confidence: 94%
“…In a WES of smoking phenotypes in up to 749,459 individuals, Rajagopal et al 305 found that LOF mutations in CHRNB2, encoding the β2 subunit of the α4β2 nicotinic acetylcholine receptor, were associated with a 35% lower risk of heavy smoking. Darrah et al 306 found by GWAS that AGTR2 deletion or antagonism prevented pulmonary cystic fibrosis and is expected to be a novel therapeutic target for pulmonary cystic fibrosis.…”
Section: Othersmentioning
confidence: 99%
“…A few examples of relevant targets are given below. In a WES of smoking phenotypes in up to 749,459 individuals, Rajagopal et al 305 . found that LOF mutations in CHRNB2 , encoding the β2 subunit of the α4β2 nicotinic acetylcholine receptor, were associated with a 35% lower risk of heavy smoking.…”
Section: Drug Development Of Targets Based On Gwas Wgs and Wes Discov...mentioning
confidence: 99%